On the identity of Bufo diptychus Cope, 1862 (Anura: Bufonidae) - Lavilla, Esteban O.; Brusquetti, Francisco (Zootaxa, 2018)
The enigmatic toad Bufo diptychus was described by Cope (1862) based on a single individual (USNM 5841, now lost) of about 25 mm of SVL, collected during the expedition to La Plata River and tributaries, conducted by Captain Page between 1853 and 1856. As no dwarf species of toad was ever recorded in the surveyed area, and based on some tips that arise from Page’s narrative, we postulate that the description was based on a toadlet. With this hypothesis in mind, we compared Cope’s characterization of B. diptychus with juveniles of all species of Rhinella present in the region, finding an exact match in almost all characters shown by the juveniles of the common “cururú” or “rococo” toad, Rhinella schneideri (Werner 1894). Henceforth, we postulate that R. schneideri is a junior synonym of B. diptychus, under the combination Rhinella diptycha (Cope 1862).